RELATIONSHIP BETWEEN MANDIBULAR AMPLITUDE AND KINESIOPHOBIA IN PATIENTS WITH MAXILLOFACIAL FRACTURE: CASE REPORT - Inácio, Iasmin Antunes de Figueiredo; Araújo, Maria Eduarda Barros Souza; de Sousa, Laura Sales; de Morais, Carla Samarina Simoes; Monteiro, Isabel de Oliveira; Rela, Maíra de Oliveira Viana (Seven Editora, 2025)
Objective: To investigate the relationship between mandibular range of motion (ROM) and kinesiophobia in patients with maxillofacial fractures. Methodology: Descriptive, observational study in the form of a case series report, conducted at the Núcleo de Atenção Médica Integrada from September to October 2022, approved by ethics committee protocol 5.641.381. The assessment included a form with sociodemographic data, fracture characteristics, and main complaints, followed by a physical examination in which pain was quantified using the VAS, sensitivity using microfilaments, and mandibular ROM—measured in mouth opening, protrusion, and right and left lateral deviation using a caliper. Kinesiophobia was assessed using the Tampa Scale for Kinesiophobia for TMD, and functional limitation using the Mandibular Function Impairment Questionnaire. Results: Only one patient presented a mandibular fracture, while the others underwent orthognathic surgery. In the assessment, Case 1 showed: mouth opening 11 mm, RLD 1 mm, LLD 3 mm, protrusion 0 mm; Case 2: mouth opening 4 mm, RLD 0 mm, LLD 1 mm, protrusion 0 mm; Case 3: mouth opening 18 mm, RLD 4 mm, LLD 5 mm, protrusion 2 mm. All patients reported moderate pain, with the most frequent complaints being movement limitation, hypoesthesia, and edema. Cases 1 and 2 showed severe kinesiophobia, and Case 3 presented moderate kinesiophobia. Conclusion: Patients with reduced mandibular movements exhibit increased kinesiophobia, along with edema and pain. DOI: https://doi.org/10.56238/sevened2025.036-124